EVOLUTION OF US REHABILITATION POLICY IN THE 1950S–1980S: INTERSTATE PATERNALISM, MEDICAL PRACTICE, AND CIVIC ACTIVISM - Fedinskyi, Oleksii (Sworld-Us Conference proceedings, 2025)
The article examines the stages of development of the rehabilitation system in the USA in the 1950s–1980s and outlines the social and political prerequisites for the institutional support of people with disabilities. Special attention is paid to the trans